The Efficacy of a Mobile Application-Based Cognitive Behavioral Therapy (CBT) in Reducing Anxiety and Depression Symptoms Among Young Adults in the Post-COVID-19 Pandemic: A Randomized Controlled Trial - Kusumawati, Prima Dewi; Koesnadi; Fonnie Kuhu; Reni Nurhidayah; Yan Deivita (International Journal of Public Health Excellence (IJPHE), 2025)
The COVID-19 pandemic has significantly increased anxiety and depression prevalence among young adults globally, with Indonesia experiencing substantial mental health challenges. Mobile application-based cognitive behavioral therapy (mCBT) interventions have emerged as promising solutions to address these widespread mental health issues. Objective: This randomized controlled trial aimed to evaluate the efficacy of a mobile CBT application in reducing anxiety and depression symptoms among Indonesian young adults in the post-COVID-19 pandemic period through comprehensive qualitative analysis. Methods: A mixed-methods randomized controlled trial was conducted with 25 young adults aged 18-25 years. Participants were randomly assigned to receive either the mCBT intervention or waitlist control. Qualitative data were collected through in-depth semi-structured interviews, focus group discussions, and thematic analysis following a phenomenological approach. Results: Thematic analysis revealed six major themes: Digital Therapeutic Alliance (89 mentions), Behavioral Change Process (92 mentions), Empowerment Through Technology (76 mentions), Resilience Building (67 mentions), Social Connection in Digital Space (54 mentions), and Challenges and Barriers (43 mentions). Participants demonstrated significant improvements in coping mechanisms, stress management, and emotional regulation through the mCBT intervention. Conclusions: Mobile CBT applications show promising efficacy in addressing post-pandemic anxiety and depression among Indonesian young adults. The intervention facilitated meaningful behavioral changes, enhanced self-efficacy, and provided accessible mental health support during challenging recovery periods